Critical Examination of International Law in Western Dominance and Global Justice - Putra, Agung Tri (Department of International Relations, Universitas Brawijaya, 2025)
This article critically examines whether international law functions merely as a tool of Western hegemony or possesses the potential to evolve into a more inclusive framework for global justice. While recognizing the historical power imbalances that have shaped its development, the analysis highlights international law's transformative potential as a mechanism for fostering cooperation, peace, and justice. By exploring historical context, progress, challenges, and the ethical balance in power dynamics, the article emphasizes the pivotal contributions of non-Western scholars and nations in reshaping the global legal order. It critiques the selective application of legal norms by dominant states, particularly in conflicts like Israel-Palestine and Russia-Ukraine, which exemplify enduring ethical dilemmas and systemic inequities. Advocating for a reimagined legal framework, the article underscores the importance of integrating diverse perspectives, addressing structural inequalities, and advancing fairness and inclusivity. Through this lens, international law emerges not only as a reflection of historical inequities but as a dynamic tool for achieving global justice and equity.